THE EFFECT OF COMPETENCY ON INCREASING HUMAN RESOURCE PRODUCTIVITY AT THE PALM OIL MILL OF PT. TASIK RAJA - Sheliawati Siregar,; Sinuhaji, Yose Andre (Jurnal Silva Samalas, 2026)
This study discusses the importance of human resources as a key factor in improving productivity at the Palm Oil Mill of PT. Tasik Raja, which still faces issues related to the alignment of competencies, technical skills, and employees' work capabilities. The purpose of this research is to analyze the effect of competence on employee work productivity using a quantitative approach and an associative research design, where data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, simple linear regression, and hypothesis testing. The results show that competence has a positive and significant effect on human resource productivity, indicating that higher levels of knowledge, skills, and work attitudes lead to increased productivity; therefore, the company is advised to enhance training programs, skill development, and continuous competency evaluation to support the achievement of production targets. Keywords: Competence, Human Resource Productivity, Palm Oil.